Motivation of the students and psychological difficulties wehn learning foreign languages - I L Soseliya (Peoples' Friendship University of Russia (RUDN University), 2009)
The article discusses general characteristics of motivation of the engineer students, their success and level of difficulties when learning foreign languages, as well as tendencies of their behavior in the group and self actualization.